Thermal analysis during turning of AZ31 magnesium alloy under dry and cryogenic conditions - Danish, M. (Springer London, 2017)
In this study, the effect of both cryogenic and dry machining of AZ31 magnesium alloy on temperature and surface roughness was examined. Cryogenic machining experiments were conducted by applying liquid nitrogen at the cutting zone. The cutting parameters (cutting speed, depth of cut, and feed rate) were varied, and their effect on the results was identified. It was found that the cryogenic machining was able to reduce the maximum temperature at the machined surface to about 60 as compared with dry machining. A finite element model was developed to predict the temperature distribution at the machined surface. The simulated results showed good agreement with the experimental data. After analyzing the temperature distribution, the model also suggested that the cryogenic-assisted machining removes heat at a faster rate as to that of the dry machining. An arithmetic model using the response surface method was also developed to predict the maximum temperature at the surface during cryogenic and dry machining. The analysis pointed out that the maximum temperature was greatly affected by the cutting speed followed by feed rate and depth of cut. Cryogenic machining leads to better surface finish with up to 56 reduction in surface roughness compared with dry machining. © 2017, Springer-Verlag London.